Efektivitas Metode Kooperatif Tipe-TGT Berbasis Outdoor Learning terhadap Keterampilan Menyimak Bahasa Arab Siswa Kelas 2 MI: The Effectiveness of the TGT-Type Cooperative Method Based on Outdoor Learning on Arabic Listening Skills of Grade 2 MI Students - Sekar Anggun Hairunisa; Rahmawati, Nailur; Ahmad Miftahuddin (Lisanul Arab: Journal of Arabic Learning and Teaching, 2024)
This research was motivated by a problem in learning Arabic for 2nd grade students of MI Hidayatul Insan Karanganyar. To understand the problems faced in learning Arabic in grade 2 students of MI Hidayatul Insan Karanganyar, it is necessary to look at the characteristics of student development at that age. Grade 2 elementary school students are still in the developmental stage where play is the main activity. They often have trouble sitting still, lose focus easily, and prefer physical activity as well as interactive. The problems that arise are low ability to collaborate and communicate in study groups, feeling bored learning in class, and lack of motivation when learning methods are monotonous and do not involve play activities. This makes learning less effective. This can affect students' listening skills. Therefore, a more creative method is needed, where the method involves students more in learning so that students can be more active in learning. This study aims to identify the effectiveness of the application of the Outdoor Learning-based TGT-type cooperative method on Arabic listening skills in grade 2 students of MI Hidayatul Insan Karanganyar. This study is a quantitative research with an experimental research design. Data collection techniques use tests and non-tests. The test instruments used are pretest and postest. As for non-tests, including interviews, observations, questionnaires, and documentation. Data analysis techniques are in the form of normality tests, homogeneity tests, and hypothesis tests. This study shows that the cooperative method of TGT type based on outdoor learning is effective in improving the Arabic listening skills of 2nd grade students of MI Hidayatul Insan Karanganyar. The average pretest and posttest scores of the control class were 66.11% and 83.33%, while the average pretest and posttest scores of the experimental class were 57.22% and 83.33%. In the data analysis regarding the level of normality test, the control class and the experimental class were normally distributed. The results of the t-test using SPSS version 29 showed a significance of 0.001, which means that there was a significant increase in the results of the experimental class. This proves the positive influence of the outdoor learning-based TGT method on learning outcomes.